Corporate reorganization and the reallocation of labor in bankruptcy - Diana Bonfim; Gil Nogueira (European Central Bank (ECB), 2024)
We analyze how corporate reorganization and liquidation change labor reallocation during bankruptcy using randomized judge assignments and linked Portuguese employer-employee and firm data. Reorganization reduces the negative effect of bankruptcy on employee earnings, even with most workers leaving reorganized firms. We examine plausible mechanisms and find evidence that the retention of general skills and improved job-match quality contribute meaningfully to this effect. The average cost of labor misallocation caused by reorganization is small. However, for some workers in the least productive filers, this cost can be large, outweighing the effect on earnings.
Keywords: G33; G38; J24; J63; K39; 330; corporate reorganization; bankruptcy